Culturally Responsive Pedagogy in Practice: Learning Strategies and Character Building in Javanese Gamelan Education at an Indonesian High School - Cipto Budy Handoyo; Akbar Bagaskara (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This qualitative study investigates the strategies for teaching Javanese gamelan at SMAN 1 Kasihan Bantul in Yogyakarta, Indonesia, with a specific focus on how these strategies facilitate character education. Employing a field research design, data were collected through direct observation of gamelan lessons and semi-structured interviews with one teacher and participating students. The findings reveal a contextually designed, gradual pedagogical approach that effectively accommodates students with heterogeneous, primarily beginner, musical backgrounds. Key strategies included prioritizing student comfort and familiarization over technical mastery, selecting simple Lancaran and Ladrang repertoire with variations (racik), and integrating theory contextually into hands-on practice. This approach proved effective in boosting student motivation, engagement, and musical understanding. Beyond musical skill acquisition, the learning process served as a powerful medium for instilling character values such as mutual respect (e.g., through customs like not stepping over instruments), discipline and emotional regulation (through ensemble cohesion), and inclusive leadership (symbolized by the kendang player's role). The study concludes that the gamelan program at SMAN 1 Kasihan Bantul offers an integrative, culture-based model for arts education, relevant to both music pedagogy and local cultural preservation in secondary schools.